Research on the Strategy of Improving Rural E-commerce Participation: A Case Study of Jiaohe City, Jilin Province - Wang, Kaixuan (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of e-commerce, rural e-commerce, as a new driving force to promote rural economic growth, has attracted much attention. Taking Jiaohe City, Jilin Province as an example, this paper discusses the current situation and challenges of local rural e-commerce development through field research and data analysis, and proposes specific strategies to enhance the participation of rural e-commerce, aiming to provide reference and reference for the development of rural e-commerce in similar regions.